MANAGEMENT OF ADVERTISING OF PHARMACEUTICAL BRANDS - Подзігун, Світлана (Modern engineering and innovative technologies, 2023)
The development of the pharmaceutical industry and the pharmaceutical market in Ukraine is important not only for the economic, but also for the social and even political aspects of the life of Ukrainian society. In the conditions of tough market competit